Investigating the Impacts of Land Use/Cover Changes on the Stream Flows of Muga Watershed - Yasab, Natnael; Dilnesa, Walelgn (International Journal of Scientific Research in Civil Engineering, 2018)
Land use /land cover change have been responsible for altering the hydrological responses of watersheds leading to impact of the stream flows. Various water resource project planning and implementation will require knowledge of the extents of these changes on watershed hydrology. This study is mainly focusing on the investigation of the impacts of land use / land cover changes on the stream flow of Muga watershed which is located in the East Choke Mountains watersheds, Upper Blue Nile Basin, East Gojjam Zone, Amhara Region, Ethiopia. Soil and Water Assessment Tool (SWAT) model were used it investigate the impact of land cover change on the stream flow. For this study SWAT Simulation is used in identifying the most vulnerable sub basins to the stream flow and sediment load changes of Muga watershed. The model was calibrated and validated using historic Stream flow data. The model was calibrated using stream flow data from 1993 to1998, validated from 1999 to2002. The R2 and NSE values were used to examine model performance and the result indicates 0.81 and 0.87 to R2 and 0.80 and 0.86 to NSE during calibration and validation respectively. The result of this analysis indicated that the mean monthly stream flow for wet months had increased by 17.75 m3/s while the dry season decreased by 12.76m3/s during the 1995-2013 period due to the land use and land cover change. The highest annual surface runoff was attributed by sub basin 5 whereas sub basin 6 contributes the highest ground water respectively for 1995, 2003 and 2013 land cover maps. In terms of sediment yield, sub basin 1 contributes a maximum load for the study periods.